2018
DOI: 10.17219/dmp/96290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the early effects of the low-level laser therapy versus intra-articular steroids on temporomandibular joint acute osteoarthritis in rats: A histochemical, molecular and imaging evaluation

Abstract: Background. Osteoarthritis (OA) is a serious degenerative joint disease. It is one of the main causes of disability in the world. Current treatment modalities have numerous side effects. Subsequently, health experts are looking for alternative therapies. Objectives. The aim of the study was to evaluate the early effects of low-level laser therapy (LLLT) vs intra-articular (IA) corticosteroids (CS) on acute temporomandibular joint osteoarthritis (TMJOA). Material and methods. Sixty rats were divided into 3 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…TMJ total prosthesis is schematically shown in Figure 4. Finally, He et al reported the potential of the use of low-intensity pulsed ultrasound for the early protection of cartilage [42], and AbuBakr et al reported the potential effectiveness of low-level laser therapy [5], which is used to relieve pain in various musculoskeletal disorders [69]. This therapy is known for its stimulatory effects on tissue metabolism and its ability to modulate the inflammatory process after injury.…”
Section: Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…TMJ total prosthesis is schematically shown in Figure 4. Finally, He et al reported the potential of the use of low-intensity pulsed ultrasound for the early protection of cartilage [42], and AbuBakr et al reported the potential effectiveness of low-level laser therapy [5], which is used to relieve pain in various musculoskeletal disorders [69]. This therapy is known for its stimulatory effects on tissue metabolism and its ability to modulate the inflammatory process after injury.…”
Section: Treatmentsmentioning
confidence: 99%
“…Most studies included in this literature review used animal models [5,6,8,11,13,36,38,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]57]. The most commonly investigated animals were mice and rats [5,8,11,13,36,38,[41][42][43][44][45][46][47][48][49][51][52][53][54]57]. One study was performed on rabbits [6].…”
Section: Models For the Study Of Tmjoamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DXM pretreatment or post-treatment of bovine explants inhibits GAG loss and increases PG synthesis in cartilage explants exposed to TNFα, preventing cartilage degradation [ 36 ]. GCs also restored the decreased content of total GAGs in rats temporomandibular joints in an in vivo model of acute temporomandibular joint osteoarthritis [ 37 ]. A similar result was shown for rat knee joints, where DXM administration at a dose of 1 mg/kg immediately prior to TNFα injection prevented TNFα-induced degradation of CSPG aggrecan and the release of aggrecanase-generated aggrecan fragments from the articular cartilage into the synovial fluid [ 38 ].…”
Section: Effects Of Gcs On Pg Expression and Gag Content In Normal Ti...mentioning
confidence: 99%